An Examination of Idiographic Networks of Posttraumatic Stress Disorder Symptoms. Issue 1 (26th February 2020) - Reeves, Jonathan W.; Fisher, Aaron J.
Abstract: Although the application of network theory to posttraumatic stress disorder (PTSD) has yielded promising insights, the lack of equivalence between inter‐ and intraindividual variation limits the generalizability of these findings to any one individual with PTSD. Instead, a better understanding of how PTSD symptoms occur and vary over time within an individual requires exploring the idiographic network structure of PTSD. To do so, the present study used an intensive repeated‐measures design to estimate intraindividual networks of PTSD symptoms on a person‐by‐person basis. Participants were 20 individuals who met criteria for PTSD and completed daily surveys assessing PTSD symptoms; surveys were completed four times per day for approximately 30 days. Employing a recently validated method provided by Fisher, Reeves, Lawyer, Medaglia, and Rubel (2017), we used these data to estimate a contemporaneous and temporal network of PTSD symptoms for individuals on a person‐by‐person basis. We then calculated centrality metrics to determine the relative importance of each symptom in each idiographic network. Across all contemporaneous networks, negative trauma‐related cognitions and emotions were most commonly the most central symptoms. Further, across all temporal networks, (a) negative trauma‐related emotions were the most common driver of variation in other symptoms over time and (b) distressing trauma‐related dreams and sleep disturbance were the most common downstream consequences of variation in other PTSD symptoms over time. We also reviewed data from two randomly selected participants to illustrate how this approach could be used to identify maintenance factors of PTSD for each individual and guide individual treatment planning. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Un examen de las redes idiográficas de los síntomas del trastorno de estrés postraumáticos REDES IDIOGRÁFICAS DE TEPT Aunque la aplicación de la teoría de redes al trastorno de estrés postraumático (TEPT) ha arrojado ideas prometedoras, la falta de equivalencia entre la variación inter e intraindividual limita la generalización de estos hallazgos a cualquier individuo con TEPT. Para comprender mejor cómo se producen y varían los síntomas del TEPT a lo largo del tiempo en un individuo, es necesario explorar la estructura de red idiográfica del TEPT. Para hacerlo, el presente estudio utilizó un diseño intensivo de medidas repetidas para estimar las redes intraindividuales de los síntomas de TEPT en función de cada persona. Veinte personas ( N = 20) que cumplieron con los criterios para el TEPT completaron encuestas diarias para evaluar los síntomas del TEPT cuatro veces al día durante aproximadamente 30 días. Empleando un método validado recientemente, provisto por Fisher, Reeves, Lawyer, Medaglia y Rubel (2017), usamos estos datos para estimar una red contemporánea y temporal de síntomas de TEPT para cada individuo, persona por persona. Luego calculamos las métricas de centralidad para determinar la importancia relativa de cada síntoma en cada red idiográfica. En todas las redes contemporáneas, las cogniciones y emociones negativas relacionadas con el trauma tendieron a ser más comúnmente los síntomas más centrales. Además, en todas las redes temporales, (a) las emociones negativas relacionadas con el trauma fueron el impulsor más común de variación en otros síntomas a lo largo del tiempo y (b) los sueños angustiantes relacionados con el trauma y las alteraciones del sueño fueron las consecuencias posteriores más comunes de la variación en otros síntomas de TEPT con el tiempo. Finalmente, también revisamos los datos de dos participantes seleccionados al azar para ilustrar cómo este enfoque podría usarse para identificar los factores de mantenimiento del TEPT para cada individuo y guiar la planificación del tratamiento individual. Palabras clave: trastorno de estrés postraumático, análisis de redes, investigación idiográfica, medidas de centralidad 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 An examination of idiographic networks of posttraumatic stress disorder symptoms Traditional Chinese 標題: 檢視創傷後壓力症症狀的個殊性網絡 撮要: 創傷後壓力症(PTSD)研究運用網絡理論所得的發現, 看來不俗。然而, 缺乏人際間變化及個人變化的等價因素, 限制了我們把那些研究發現普遍化並用於任何一位PTSD患者。要加以理解患者的PTSD症狀如何隨時間出現和轉變, 則要探討PTSD的個殊性網絡結構。因此, 本研究採用密集的重複測量設計, 逐一檢視樣本, 以預測個人的PTSD症狀網絡。共有20名符合患PTSD準則的人士(N = 20), 在約30天內, 每天進行PTSD症狀評估四次。我們運用Fisher, Reeves, Lawyer, Medaglia, and Rubel (2017)近期驗證的方法, 以收集的數據, 基於每個人逐一預測同期的及時間的PTSD症狀網絡, 然後計算中心性指標, 找出每個個殊性網絡裡各個症狀的相對重要性。在所有同期網絡中, 負面的創傷相關認知與情緒傾向最普遍為最中心症狀。再者, 在所有時間網絡中, (a) 負面的創傷相關情緒, 對其他症狀是隨時間最普遍的變化驅動因素;(b) 創傷相關、引起悲痛的夢境及睡眠障礙, 是其他PTSD症狀隨時間最普遍的變化下游後果。最後, 我們亦審視兩個隨機選出的樣本數據, 闡釋這個方法可如何用以找出每位患者的PTSD維持因素, 並為個人治療的規劃提供指導。 關鍵字:創傷後壓力症、網絡分析、個殊性研究、中心性測量 Simplified Chinese 标题: 检视创伤后压力症症状的个殊性网络 撮要: 创伤后压力症(PTSD)研究运用网络理论所得的发现, 看来不俗。然而, 缺乏人际间变化及个人变化的等价因素, 限制了我们把那些研究发现普遍化并用于任何一位PTSD患者。要加以理解患者的PTSD症状如何随时间出现和转变, 则要探讨PTSD的个殊性网络结构。因此, 本研究采用密集的重复测量设计, 逐一检视样本, 以预测个人的PTSD症状网络。共有20名符合患PTSD准则的人士(N = 20), 在约30天内, 每天进行PTSD症状评估四次。我们运用Fisher, Reeves, Lawyer, Medaglia, and Rubel (2017)近期验证的方法, 以收集的数据, 基于每个人逐一预测同期的及时间的PTSD症状网络, 然后计算中心性指标, 找出每个个殊性网络里各个症状的相对重要性。在所有同期网络中, 负面的创伤相关认知与情绪倾向最普遍为最中心症状。再者, 在所有时间网络中, (a) 负面的创伤相关情绪, 对其他症状是随时间最普遍的变化驱动因素;(b) 创伤相关、引起悲痛的梦境及睡眠障碍, 是其他PTSD症状随时间最普遍的变化下游后果。最后, 我们亦审视两个随机选出的样本数据, 阐释这个方法可如何用以找出每位患者的PTSD维持因素, 并为个人治疗的规划提供指导。 关键词:创伤后压力症、网络分析、个殊性研究、中心性测量